2019
DOI: 10.24869/psyd.2019.106
|View full text |Cite
|
Sign up to set email alerts
|

Ffective Temperament and Seasonality in Bipolar Disorder

Abstract: Background: Both affective temperaments and seasonality impact on the illness course in bipolar disorder (BD). This exploratory study aims to investigate the link between seasonality and affective temperament in BD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Our sample consisted of 503 (71%) patients with BDI and 205 (29%) with BDII ( Table 1). Of all patients, 16.5% (N = 117) fulfilled DSM-5 seasonal pattern criteria and 13.5% (N = 96) fulfilled DSM-IV-TR criteria ( Table 1). The sample was further divided according to DSM-5 seasonality into two groups: without and with seasonality ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our sample consisted of 503 (71%) patients with BDI and 205 (29%) with BDII ( Table 1). Of all patients, 16.5% (N = 117) fulfilled DSM-5 seasonal pattern criteria and 13.5% (N = 96) fulfilled DSM-IV-TR criteria ( Table 1). The sample was further divided according to DSM-5 seasonality into two groups: without and with seasonality ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…11 Indeed, seasonality is associated with a positive family history of BD 12 and it also shows heritability in twin studies. 13,14 Several mechanisms might underlie seasonality, involving photoperiod and sunlight exposure, 15 temperament, 16 chronotype, 17 and gender. 18 Globally, the clinical correlates of seasonality broadly point toward a more severe clinical profile.…”
Section: Introductionmentioning
confidence: 99%
“…Insomnia, akathisia, constipation, anxiety, nausea and vomiting are reported to occur with cariprazine treatment in patients with negative symptoms of schizophrenia ( Table 3 ). However, the side effects have lower occurrence rate than other available SGAs ( 86 ). Discontinuation of cariprazine due to treatment-emergent adverse events is as low as 9% ( 62 ).…”
Section: Cariprazine: a Novel Third Generation Antipsychoticmentioning
confidence: 97%
“…Several studies have focused on temperament assessments in individuals diagnosed with MDD [15][16][17] or with BD specifically [18][19][20][21][22][23][24], or have considered mood disorders together using TCI [25,26] or TEMPS [1,[27][28][29][30]. Such studies have revealed differences between mood disorder patients and controls, including unaffected family members, with suggestive differences between BD and MDD patients and possibly between BD-1 and BD-2 patients based on ratings of cyclothymic, hyperthymic, and irritable temperaments, in particular, as well as ratings of harm-avoidance [1,[31][32][33].…”
Section: Introductionmentioning
confidence: 99%